Recruitment of Immigrant Hispanic Mothers in Research: An Application of the EERC Guidelines. (January 2020) - Cartagena, Diana; Matsuda, Yui; McGrath, Jacqueline M.
Introduction: Innovative and culturally sensitive strategies are needed to promote research participation among minorities and develop targeted interventions aimed at decreasing health disparities. The purpose of this article is to illustrate application of the EERC (evaluate, engage, reflect, and carefully match) guidelines in facilitating participant recruitment in a study exploring infant feeding practices of Hispanic mothers.Methodology: Retrospective application of the EERC guidelines assessed using data extracted from the researcher-study recruitment field notes. A systematic categorical process was used to determine if each of the guidelines' key concepts were incorporated in the recruitment process.Results: Successful recruitment of 62 immigrant Hispanic mothers (approximately 82% of target goal) was accomplished through implementation of most of EERC criteria (90%) in planning and recruitment phases of the study.Discussion: Application of EERC guidelines facilitates recruitment of minority populations. Enhanced participant recruitment assists in assessment of population-unique conditions and targeted interventions leading to disease prevention and improved outcomes.